Modelling of the hardening and finishing stages of grind-hardened workpieces. Issue 1 (January 2016) - Ortega, Naiara; Alonso, Unai; Sánchez, José; Pombo, Iñigo; Plaza, Soraya; Izquierdo, Borja
Abstract Grind-hardening is a manufacturing process that uses the heat generated within the grinding zone in order to produce surface hardening. After the process, workpieces present dimensional inaccuracies and a poor surface finish. Thus, a finishing grinding operation has to be carried out. For a successful implementation of the whole process, two problems have to be solved. Firstly, the desired hardened depth has to be achieved in the hardening stage. Secondly, surface softening has to be controlled during the finishing stage. The objective of this work is to address the modelling of the whole process so that the experimental effort during its set up is reduced. To do this, firstly, a thermal model is developed for the estimation of the hardened depth. This model considers the heat evacuated by the chips in a simplified way and takes into account the heat consumed by the fast austenitization process through an original methodology. Secondly, a model is proposed for the estimation of surface softening during finishing grinding. A methodology is presented for the prediction of surface hardness under non-isothermal tempering. Both models are calibrated and validated for the AISI 1045 steel, and the predicted results are in agreement with the experimental data for the studied grinding regimes. In this regard, the grind-hardening model predicts the hardness penetration depth (HPD) precisely for HPD values over 0.2 mm. The finishing model estimates the surface hardness after the finishing of the workpiece with an error lower than 6 %.